KNOWLEDGE OF BASIC LIFE SUPPORT AMONG SENIOR HIGH SCHOOL STUDENTS AT SMA BUDI MURNI 2 MEDAN IN 2026 - Herlisa Patrecia Siahaan; Indra Hizkia Perangin-angin; Sry Rumondang Sitindaon (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2026)
Background: Basic Life Support is essential for high school students as a form of preparedness in emergency situations such as cardiac arrest, respiratory arrest, syncope, and choking. Limited knowledge of Basic Life Support among students may lead to delays in providing first aid and reduce the chances of survival in emergency cases. Purpose: This study aimed to describe the level of knowledge of eleventh-grade high school students regarding Basic Life Support at SMA Budi Murni 2 Medan in 2026. Methods: This study used a descriptive quantitative design. The population consisted of 222 eleventh-grade students, with 69 respondents selected through stratified random sampling. Data were collected using a standardized questionnaire consisting of 22 multiple-choice questions covering the definition, indications, principles, procedures, and criteria for terminating Basic Life Support. Data were analyzed using univariate analysis in the form of frequency distribution and percentages. Results: The results showed that most respondents were 16 years old (49.3%) and female (59.4%). Based on the level of knowledge, 36 respondents (52.2%) had sufficient knowledge, 24 respondents (34.8%) had poor knowledge, and 9 respondents (13.0%) had good knowledge. Knowledge regarding the definition, indications, principles, and criteria for terminating Basic Life Support was mostly in the good category, while knowledge regarding the procedures of Basic Life Support according to standard operating procedures was mostly in the sufficient category. Conclusion: The knowledge level of eleventh-grade students regarding Basic Life Support at SMA Budi Murni 2 Medan was predominantly in the sufficient category. Continuous education and simulation-based training on Basic Life Support are recommended to improve students’ preparedness in handling emergencies at school.